Impact of Car Arrival/Departure Patterns on EV Parking Lot Energy Storage Capacity - Guner, Sitki; Ozdemir, Aydogan; Serbes, Gorkem (IEEE, 2016)
Development and implementation of electrified transportation systems, particularly those that integrate with renewable-based vehicle charging systems are supposed to continue attracting the interest of the researchers in the future. Electric utilities have to develop integrated solutions to take the advantage of the opportunities that transportation electrification offers, in addition to design and planning of their supply needs. In this context, storage capacity of electric vehicles (EVs) offer a new and effective distributed storage capacity for evolving power grids. It is clear that an effective storage can be achieved by aggregating the single EVs. Commercial car parks and parking lots of several public and private companies can be used for these purposes. This paper presents improved car arrival/departure patterns to asses more realistic storage capacity models for an EVPL. Real car arrival/departure data of a representative PL, provided by The Chief Management of Istanbul Car Parking Corporation is used in the studies. In addition, future car arrival/departure patterns are estimated using the available data and PL storage capacity is obtained for those future patterns.
Keywords: Distributed Energy Resources; Electric Vehicle; Parking Lot; Monte-Carlo Simulation; Kernel Density Estimator; ELECTRIC VEHICLES; SYSTEM; Energy & Fuels; Engineering